Purificação e caracterização parcial de uma lectina pró-inflamatória de sementes de Bauhinia bauhinioides MART - Silva, Helton Colares da (2010)
A new galactose-specific lectin, named BBL, was purified from seeds of the Caesalpinoideae plant, Bauhinia bauhinioides, by precipitation with solid ammonium sulfate followed by two steps of ion exchange chromatography, and its pro-inflammatory activity was evaluated. The lectin haemagglutinated rabbit and humans erythrocytes (native and treated with proteolytic enzymes), which occurred independent on presence of divalent cations, was stable at 60 °C for 60 min, had an optimum pH between pH 8.0 and 9.0 and was inhibited after incubation with D-galactose and its derivatives, especially α-methyl-D-galactopyranoside. The pure protein was found to have a molecular mass of 31 kDa by SDS–PAGE and 28,305 Da by electrospray ionization mass spectrometry. The s.c. injection of BBL induced dose-dependent paw edema at all doses tested, an effect that occurred via carbohydrate site interaction and that was significantly reduced by L-NAME, indicating the important participation of nitric oxide in the late phase of the edema induced by BBL. These findings indicate that this lectin can be used as a tool to better understand the mechanisms involved in inflammatory responses.